1998
DOI: 10.1016/s1010-7940(98)00164-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced renal failure following thoracoabdominal aortic aneurysm repair by selective perfusion1

Abstract: Objectives: Renal failure and visceral ischemia are feared complications following thoracoabdominal aortic aneurysm (TAAA) repair, significantly contributing to mortality. This prospective study describes volume-and pressure-controlled perfusion of the renal and visceral arteries during TAAA surgery. Methods: In 73 consecutive patients (mean age 59 years), TAAA repair (27 type I, 28 type II, 8 type III and 10 type IV) was performed, using retrograde and selective organ perfusion. Sixteen patients had impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…Currently Coselli's group perfuses the celiac and superior mesenteric arteries at 200-300 ml/min under mild hypothermia [16], which seems similar to ours. Jacobs and co-workers advocated the pressure-controlled perfusion for better outcome in visceral function [17]. They perfuse visceral branches at a flow of 60-210 ml/min per branch and the renal arteries at 200-280 ml/min, which also seems not far different from our protocol.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Currently Coselli's group perfuses the celiac and superior mesenteric arteries at 200-300 ml/min under mild hypothermia [16], which seems similar to ours. Jacobs and co-workers advocated the pressure-controlled perfusion for better outcome in visceral function [17]. They perfuse visceral branches at a flow of 60-210 ml/min per branch and the renal arteries at 200-280 ml/min, which also seems not far different from our protocol.…”
Section: Discussionmentioning
confidence: 92%
“…They perfuse visceral branches at a flow of 60-210 ml/min per branch and the renal arteries at 200-280 ml/min, which also seems not far different from our protocol. On the other hand, it was pointed out that too much flow through a small diameter catheter might lead to jeopardized rheological properties of the blood [12,17]. We reported that our original heparincoated 10 mm tube circuit with four 6 mm side-arm branches could provide a free flow of 230 ml/min at 60 mmHg and 335 ml/min at 100 mmHg through a 12 F balloon [8].…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing circulating blood volume may decrease the risk of renal complications by inhibiting the formation of renal vasoconstrictive compounds [1]. Other methods that may be used to protect renal function during aortic cross-clamping include distal aortic perfusion and selective pressure-controlled and flow-volume-controlled renal perfusion [17]. Other, more controversial techniques include administering intravenous mannitol, furosemide, dopamine, fenoldopam, and ACE inhibitors.…”
Section: Renal Effectsmentioning
confidence: 99%
“…Adjunctive end-organ protective measures, if used during the repair of a TAAA, markedly decrease the likelihood of renal, mesenteric, and spinal ischemia, with resultant decrease in the risk of visceral injury, paraplegia, and paraparesis. These adjunctive measures include distal aortic perfusion via left heart bypass, profound hypothermic cardiopulmonary bypass, selective perfusion of renal and visceral arteries, reimplantation of vessels between intercostals and lumbar arteries, cerebrospinal fluid drainage, and instillation of intrathecal papaverine for high-risk patients [15][16][17][18]. Among all TAAAs, Crawford type II aneurysms have of the highest surgical morbidity and mortality rates.…”
Section: Surgical Managementmentioning
confidence: 99%